Respiratory health - Pokorski, Mieczyslaw (Advances in Experimental Medicine and Biology, 2015)
The tracheobronchial tree is open to the environment surrounding the body. Respiration has thus the essential bearing on general morbidity, vulnerability to disease and immunity. Further, respiratory function shapes the neuropsychological responses to succumbing to disease, controls the mind-to-body interaction and sets the perception of quality of life. The chapters of this book deal with the preventable drivers of poor respiratory health, the role of health information technology, the improvement in health care delivery and the integration of respiratory health and behavioral health services. Innovative strategies to promote prevention, care coordination and care integration as well as to align disease acceptance and quality of life measures also are tackled. Maintaining respiratory health is of rising research interest as a way of preventing a disease or a non pharmacological therapeutic succor. The book will be of interest to clinicians, family practitioners and medical researchers.